Digital Media as a Symbol of Piety: The Use of Smart Hafiz in Muslim Middle-Class Families - Amalia, Milda; Assegaf, Abd Rachman; Arifin, Achmad Zainal (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study explores the use of Smart Hafiz, an interactive digital media device, in middle-class Muslim families in Yogyakarta as a symbol of piety for children. The study aims to understand how Smart Hafiz is integrated into daily life and how its use reflects the religious aspirations as well as the social identity of middle-class Muslim families. By using a qualitative approach through in-depth interviews and participant observations conducted in 2024. This study found that Smart Hafiz is not only used as a means of religious learning, but also as a symbolic reinforcement that piety is not enough to be practiced, but supported by religious symbols. These findings show that digital media plays an important role in shaping religious practices in the modern era, as well as reflecting the dynamics of interaction between religion, technology, and social classes. This research contributes to the study of media and religion, digital media is currently an alternative need for the piety of Muslim middle-class families.